Source characteristics of the aftershocks of the Wenchuan and Lushan earthquake sequences in the Longmen-Shan fault zone - Wang, Zibo; Liu, Ruifeng; Liu, Wei (Frontiers in Earth Science, 2023)
After the occurrence of the 2008 Wenchuan Mw 7.9 earthquake, the Longmen-Shan fault zone exhibits highly active seismicity. In the years between 2008 and 2022, successive moderate magnitude aftershocks followed in the region. In this study, we used high-quality seismic data from the National Earthquake Data Center of China to estimate the source parameters of 184 moderate magnitude events (Mw 3.9–6.2) in the Longmen-Shan Fault zone. The dataset comprised the aftershocks of two sequences that occurred in the area, including the 2008 Wenchuan earthquake sequence and the 2013 Lushan earthquake sequence. They have been classified according to their focal mechanism. First, our results suggested that the values of apparent stress varied from approximately 0.1–11 MPa, which are higher than the global average. The strike-slip earthquakes have the highest average apparent stress among the types of earthquakes. The above results indicate that the moderately high levels of energy release from earthquakes in this region could result in high ground shaking potential. This behavior may be associated with the high stress accumulation and the strong deformation characteristics in the intraplate environment of the Longmen-Shan Fault zone. The values of the stress drop vary from approximately 0.24–39 MPa and appear to show a slightly increasing trend with the seismic moment. The stress drop level of the Lushan earthquake sequence is higher than the mean value of intraplate earthquakes, while the Wenchuan earthquake sequence is typical of intraplate earthquakes. Second, we investigate the radiated energy enhancement factor (REEF) to quantify the source complexities. The results show that the earthquakes have REEF values between 1.2 and 7.1, and most events are consistent with expectations based on the Brune ω-square model. There exist differences in the source complexity of earthquakes within the source area, and the average ω-square source model could result in an unreliable estimate of the radiated seismic energy of some events. The observation of moderate magnitude earthquakes suggests that the availability of different source parameters will help us to assess the seismic hazard and predict the shaking potential in the earthquake area.